Phytochemical screening, mineral composition and in vitro antioxidant activities of Pterocarpus mildbraedii leaves - Usunobun, Usunomena; V. Chinwe, Igwe (International Journal of Scientific World, 2016)
Background: Pterocarpus mildbraedii is used in some Nigerian tribes in the treatment of headaches, pains, fever, convulsions, and respiratory disorders. This study was carried out to ascertain the phytochemicals, minerals and in vitro antioxidant activities of Pterocarpus mildbraedii leaves.Methods: Qualitative phytochemical screening was carried out using standard procedures while Mineral analysis was carried out using Atomic Absorption Spectrophotometer (AAS). Also, antioxidant activities of Pterocarpus mildbraedii leaves were evaluated using reducing power ability and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays.Results: Result on phytochemicals reveals the presence of flavonoids, saponins, alkaloids, tannins. Mineral analysis showed calcium (1283mg/kg) to be higher in concentration and manganese (4mg/kg) least in concentration (4mg/kg). Other analysed minerals include sodium (603mg/kg), potassium (1048mg/kg), magnesium (778mg/kg), zinc (25mg/kg), iron (146mg/kg), phosphates (1002mg/kg), etc. In vitro antioxidant activity results show that Pterocarpus mildbraedii possess potent but dose-dependent reducing power ability and free radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals.Conclusion: The presence of phytochemicals such as flavonoids, saponins, alkaloids and tannins in Pterocarpus mildbraedii provides some biochemical basis for the ethno pharmacological uses of the plant. Also the information provided in this research study may help to spread the ethno botanical uses of Pterocarpus mildbraedii leaves to other parts of the World. The findings clearly demonstrate that Pterocarpus mildbraedii leaves have promising antioxidant property and needs further evaluation to exploit its therapeutic potential.